Pig’s behavioral response in nursery and growth phases to environmental enrichment objects - Foppa, Luciana; Caldara, Fabiana R.; de Moura, Rafael; Machado, Simone P.; Nääs, Irenilza A.; Garcia, Rodrigo G.; Gonçalves, Liliane M. P.; de Oliveira, Geyssane F. [UNESP] (Instituto Nacional de Investigacion y Tecnologia Agraria y Alimentaria (INIA), 2018)
The objective of this research was to evaluate the effect of environmental enrichment on the behavior of pigs in nursery and growth phases. (i) Ninety animals (females, 65 days, 25 kg) were divided into three treatments (T1-Pen enriched with objects made of destructible material by the animal, T2-Pen enriched with objects made of non-destructible material by the animal, T3-Pen without environmental enrichment objects-control treatment)-in a completely randomized design and reference of the animals by objects of enrichment of different colors (red, blue or yellow). (ii) males, 25 days old, 7 kg were distributed in a completely randomized design with four treatments (cloves, garlic, alternating aromas and absence of control smells) and six replicates each. (iii) determine the appropriate ratio between the number of enrichment objects and the animals present in the animals (n = 138; females; 65 days; 25 kg) were distributed in three treatments, in a completely randomized experimental design (proportion of one enrichment object for each 1511 animals or 9 animals, respectively). Environmental enrichment objects made from destructible materials are more attractive to pigs. No preference for pigs for environmental enrichment objects of specific colors was observed. Environmental enrichment objects with garlic aroma had a repellent effect. No effect was observed of alternating perfumes in the animals retaining interest in the objects since the smell of garlic acted as a repellent. Thus, the proportion of one enrichment object for each 15 pigs is sufficient to avoid problems of dispute between the animals.
Keywords: Colour preference; Olfaction; Preference; Sight; Welfare